ULTRASOUND DIAGNOSTIC APPARATUS, METHOD OF CONTROLLING ULTRASOUND DIAGNOSTIC APPARATUS, AND PROCESSOR FOR ULTRASOUND DIAGNOSTIC APPARATUS - YAMAMOTO Katsuya (2020)
An ultrasound diagnostic apparatus (1) is provided with: a B-mode processing unit (6) for generating a B-mode image in which an image of a blood vessel is captured on the basis of a reception signal obtained by transmitting and receiving ultrasonic waves to and from a subject; a display device (9) for displaying the B-mode image; a blood vessel wall detection unit (10) for detecting a blood vessel wall on the basis of the B-mode image; a gate setting unit (11) for setting a Doppler gate within the blood vessel in the B-mode image; a Doppler processing unit (7) for acquiring Doppler data within the Doppler gate; a blood flow velocity calculation unit (13) for calculating a blood flow velocity on the basis of the Doppler data; and a blood flow rate measurement unit (12) for measuring a blood flow rate on the basis of the detected blood vessel wall and the calculated blood flow velocity. The ultrasound diagnostic apparatus (1) automatically measures the blood flow rate on the basis of a predetermined initiation trigger. L'invention concerne un appareil de diagnostic à ultrasons (1) comprenant : une unité de traitement en mode B (6) destinée à générer une image en mode B dans laquelle une image d'un vaisseau sanguin est capturée sur la base d'un signal de réception obtenu par émission et réception d'ondes ultrasonores vers et depuis un sujet ; un dispositif d'affichage (9) destiné à afficher l'image en mode B ; une unité de détection de paroi de vaisseau sanguin (10) destinée à détecter une paroi de vaisseau sanguin sur la base de l'image en mode B ; une unité de réglage de porte (11) destinée à régler une porte Doppler au sein du vaisseau sanguin dans l'image en mode B ; une unité de traitement Doppler (7) destinée à acquérir des données Doppler au sein de la porte Doppler ; une unité de calcul de vitesse de flux sanguin (13) destinée à calculer une vitesse de flux sanguin sur la base des données Doppler ; et une unité de mesure de débit sanguin (12) destinée à mesurer un débit sanguin sur la base de la paroi de vaisseau sanguin détectée et de la vitesse de flux sanguin calculée. L'appareil de diagnostic à ultrasons (1) mesure automatiquement le débit sanguin sur la base d'un déclencheur d'initiation prédéterminé. 超音波診断装置（１）は、被検体に対する超音波の送受信により得られる受信信号に基づいて血管が撮像されているＢモード画像を生成するＢモード処理部（６）と、Ｂモード画像を表示する表示装置（９）と、Ｂモード画像に基づいて血管壁を検出する血管壁検出部（１０）と、Ｂモード画像上の血管内にドプラゲートを設定するゲート設定部（１１）と、ドプラゲート内のドプラデータを取得するドプラ処理部（７）と、ドプラデータに基づいて血流速度を算出する血流速度算出部（１３）と、検出された血管壁および算出された血流速度に基づいて血流量を計測する血流量計測部（１２）とを備え、定められた開始トリガに基づいて血流量を自動的に計測する。